What's wrong with being a ward sister anyway? - P. MacMillan (AOSIS, 1980)
Aunt Marge was my favourite ward sister. Well, everyone called her Aunt Marge, and perhaps I remember her best because she was my first ward sister. She was a character. I can tell you - the scourge of the general medical team.